A new wave of marine evidence-based management: emerging challenges and solutions to transform monitoring, evaluating, and reporting. (13th December 2017) - Addison, P F E; Collins, D J; Trebilco, R; Howe, S; Bax, N; Hedge, P; Jones, G; Miloslavich, P; Roelfsema, C; Sams, M; Stuart-Smith, R D; Scanes, P; et al.
Abstract: Sustainable management and conservation of the world's oceans requires effective monitoring, evaluation, and reporting (MER). Despite the growing political and social imperative for these activities, there are some persistent and emerging challenges that marine practitioners face in undertaking these activities. In 2015, a diverse group of marine practitioners came together to discuss the emerging challenges associated with marine MER, and potential solutions to address these challenges. Three emerging challenges were identified: (i) the need to incorporate environmental, social and economic dimensions in evaluation and reporting; (ii) the implications of big data, creating challenges in data management and interpretation; and (iii) dealing with uncertainty throughout MER activities. We point to key solutions to address these challenges across MER activities: (i) integrating models into marine management systems to help understand, interpret, and manage the environmental and socio-economic dimensions of uncertain and complex marine systems; (ii) utilizing big data sources and new technologies to collect, process, store, and analyze data; and (iii) applying approaches to evaluate, account for, and report on the multiple sources and types of uncertainty. These solutions point towards a potential for a new wave of evidence-based marine management, through more innovative monitoring, rigorous evaluation and transparent reporting. Effective collaboration and institutional support across the science–management–policy interface will be crucial to deal with emerging challenges, and implement the tools and approaches embedded within these solutions.